John Cabot : the ongoing search for a westward passage to Asia - Rengel, Marian (New York : Rosen Pub. Group, 2002)
Examines the facts and theories surrounding the voyages taken to North America by the English explorer John Cabot in the late 1490s.
Includes bibliographical references and index.
Keywords: Cabot, John -- d. 1498?; Explorers -- North America; Explorers -- Great Britain; Explorers -- Italy; Explorers; America -- Discovery and exploration -- English; North America -- Discovery and exploration -- English; America -- Discovery and exploration -- English